Hypodontia Patterns and Natural Dental Compensation Movements. An Orthopantomographic Study - Georgeta Zegan; Loredana Golovcencu; Cristian Romanec; Gabriela Lesner (Romanian Society of Oral Rehabilitation, 2012)
The study aims to detect on orthopantomogram the hypodontia of permanent teeth, setting the hypodontia frequency patterns for each patient and on both sexes and their correlation. The study also aims to establish the persistence of temporary teeth and the remaining free space on dental arch in the case of hypodontia patterns and the amount of reduction of remaining space by dental buds' movements or by permanent teeth close to the hypodontia, as natural dental phenomena compensation. Hypodontia diagnosis was established on clinical and orthopantomogram examination on 107 patients (49 boys and 58 girls) with a mean age of 10.76 years (between 6 and 28 years). The most common hypodontia patterns were 35 hypodontia, 12-22 hypodontia, 35-45 hypodontia, 12 and 22 hypodontia. Hypodontia frequency patterns differ by sex. In the of the hypodontia patterns 35 and 35-45 it was found an increased frequency of persistent second mandibular temporary molars and the movements of the permanent teeth close to the hypodontia maintained or decreased the space for the second mandibular premolars, congenitally absent. In the case of the hypodontia pattern 12, 22, and 12-22 it was found an increased frequency of absence of the temporal lateral maxillary incisors, and the movements of the permanent teeth or dental buds close to the hypodontia have reduced or closed the space of the congenitally absent permanent maxillary lateral incisors. In this study there have been applied, for the first time some statistical techniques concerning the natural dental compensation of teeth or dental buds close to the hypodontia, specific to the patterns of hypodontia.